Development and validation of a new 18 X‐STR typing assay for forensic applications. Issue 6 (27th January 2021) - Zhang, Yinming; Yu, Zhengliang; Mo, Xiaoting; Zhao, Xingchun; Li, Wanshui; Liu, Hong; Liu, Chao; Wu, Riga; Sun, Hongyu
Abstract: With a unique inheritance pattern compared to autosomal short tandem repeats (A‐STRs), X chromosomal STRs (X‐STRs) have special usage in forensic relationship testing. In this study, we designed a multiplex amplification system (named TYPER‐X19 multiplex assay) consisting of 18 STR loci spreading from 7.837 to 149.460 Mb on the X chromosomes (DXS9895, DXS8378, DXS9902, DXS6810, DXS7132, DXS10079, DXS6789, DXS7424, DXS101, DXS6797, DXS7133, DXS6804, GATA165B12, DXS10103, HPRTB, GATA31E08, DXS8377, and DXS7423), and the amelogenin. PCR primers were marked with four kinds of fluorophores including FAM, HEX, TAMRA, and ROX. The multiplex system was optimized and tested for precision, concordance, reproducibility, sensitivity, stability, DNA mixture, and species specificity according to the conventional validation guidelines. The results indicated that the system was accurate, reliable, and sensitive enough, and was suitable for common forensic case‐type samples. In the population genetic study, a total of 148 alleles were detected at the 18 X‐STR loci in 398 Southern Han Chinese. Relatively high combined power of discrimination in male (PDm ), power of discrimination in female (PDf ), mean paternity exclusion chance in trios (MECtrio ), and mean paternity exclusion chance in duos (MECDuo ) by Desmarais were detected, and HPRTB‐DXS10103 was in linkage disequilibrium. The results suggested that the TYPER‐X19 multiplex assay was suitable for forensic applications.